Fungsi Hadist Terhadap Al – Qur’an - Ola Alifiyanti Zahra Purnama; Farhan Daffa Amrulloh; Azis Arifin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
According to experts, a hadith is a saying or action of the Prophet Muhammad SAW. In fact, the meaning of Hadith is conveying something, namely news from one person to another. Writing this journal uses a qualitative method with a library research method by looking for sources from journals, papers and books. Hadith is the second source of law after the Qur'an and Hadith is a complement to the Qur'an, the function of hadith is as a correct interpretation in the application of Islamic law. Hadith is the first reference or main source of law in Islam. Hadith also provides a view of human life.